1990
DOI: 10.1093/carcin/11.6.1033
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transfer of aflatoxin in humans

Abstract: This study quantified aflatoxin (AFB1, AFG1 and AFQ1) by enzyme-linked immunosorbent assay in human cord sera obtained at birth and in serum obtained immediately after birth from the mother. The subjects of the study were residents of Songkhla, Thailand. Of the 35 samples of cord sera, 17 (48%) contained aflatoxin in concentrations from 0.064 to 13.6, mean 3.1 nmol/ml. By comparison only two (6%) of 35 maternal sera contained aflatoxin (mean 0.62 nmol/ml). These results demonstrate transplacental transfer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(25 citation statements)
references
References 0 publications
0
24
1
Order By: Relevance
“…28 We found a highly significant negative correlation between aflatoxin levels in cord blood and birthweight and between maternal aflatoxin levels and birthweight. Unlike most reports in the literature, 9,29,30 we found a highly significant correlation between aflatoxin levels in mothers and their infants. This reflects either the speed and efficiency with which aflatoxins are transported across the placenta to the fetus or continuous ingestion of aflatoxin by the mother, thereby resulting in a steady supply of aflatoxin to the fetus.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…28 We found a highly significant negative correlation between aflatoxin levels in cord blood and birthweight and between maternal aflatoxin levels and birthweight. Unlike most reports in the literature, 9,29,30 we found a highly significant correlation between aflatoxin levels in mothers and their infants. This reflects either the speed and efficiency with which aflatoxins are transported across the placenta to the fetus or continuous ingestion of aflatoxin by the mother, thereby resulting in a steady supply of aflatoxin to the fetus.…”
Section: Discussioncontrasting
confidence: 99%
“…It is surprising therefore that a study in Thailand found aflatoxin in the blood of only two mothers, drawn immediately after the birth of 35 neonates with aflatoxins in their cord blood. 29 Others have also reported a lack of correlation between aflatoxin in cord blood and maternal blood. 9 In the latter study, 53% of 125 primigravida mothers tested prenatally were positive for aflatoxins and the same percentage from a further 59 women tested at delivery proved positive, but only one of 34 had both prenatal and postnatal exposure while 12 of 34 previously negative samples were positive at delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Aflatoxin has been detected in cord blood and breast milk in areas of Africa and Asia that have high rates of food contamination with this fungal toxin. In Thailand, 17 of 35 samples of cord sera contained aflatoxin at concentrations of 0.064-13.6 nmol/ml, whereas only 2 of 35 samples of maternal sera contained aflatoxin (Denning et al, 1990). Aflatoxin was detected in 37% of Sudanese, 28% of Kenyan, and 32% of Ghanaian breast milk samples (Maxwell et al, 1989).…”
Section: Livermentioning
confidence: 98%
“…This exposure, in the case of a developing individual, not only takes place through foodstuffs but also through mother's milk (5,6). Additionally, transplacental exposure of aflatoxin to fetus has also been reported (7). The prevailing conditions of malnourishment may also aggravate the toxic and carcinogenic potentials of aflatoxin in a developing host (34,35).…”
Section: Effects Of Afb1 On Biotransformation Enzymesmentioning
confidence: 99%